Toll-like receptor 3 activation enhances antitumor immune response in lung adenocarcinoma through NF-κB signaling pathway - Ang Li; Ang Li; Ang Li; Man Luo; Xiyao Liu; Hongjiao Wu; Hongjiao Wu; Hongjiao Wu; Xiaoguang Liu; Zhi Zhang; Xuemei Zhang; Xuemei Zhang; et al. (Frontiers in Immunology)
BackgroundToll-like receptor 3 (TLR3) is a pattern recognition receptor known to play a crucial role in the immune response to cancer. However, its effect on the efficacy of immunotherapy in lung adenocarcinoma (LUAD) remains unclear. This study aims to investigate the role of TLR3 in LUAD by examining its expression levels, prognostic significance, and impact on immune signaling pathways.MethodsWe analyzed the impact of TLR3 expression on the prognosis of lung adenocarcinoma patients using data from the Cancer Genome Atlas (TCGA) database and four additional cohorts (GSE72094, GSE30219, GSE50081 and GSE31210). Functional enrichment analyses were performed to compare molecular features between low and high TLR3 expression groups using gene set variation analysis (GSVA). We also examined the correlation between TLR3 and tumor mutation burden (TMB), immune infiltration, and PD-L1 expression. Further experimental validation was conducted using co-culture systems of LUAD cells and peripheral blood mononuclear cells (PBMCs) with PD1 inhibitors, and Western blot analysis to investigate the involvement of NF-κB signaling.ResultsTLR3 expression was significantly lower in LUAD tissues compared to normal tissues, with high TLR3 expression correlating with better survival outcomes across multiple cohorts. High TLR3 expression was associated with increased TMB and enhanced immune activation. Patients with high TLR3 expression exhibited higher immune checkpoint expression and immune cell infiltration. Experimental results showed that TLR3 agonists increased the susceptibility of LUAD cells to activated PBMCs under PD1 inhibitor therapy, inhibiting cell proliferation, migration, and invasion. Additionally, TLR3 has a strong positive correlation with MHC molecules and upregulated PD-L1 expression. NF-κB was identified as a key regulator of PD-L1 expression, with TLR3 agonists enhancing NF-κB and PD-L1 activity.ConclusionTLR3 enhances the anti-tumor immune response in LUAD by modulating NF-κB signaling and PD-L1 expression, making it a promising prognostic biomarker and therapeutic target. This study highlights the potential of TLR3 to improve immunotherapy outcomes, providing a comprehensive analysis of its role in LUAD and paving the way for novel therapeutic strategies targeting TLR3-mediated pathways.